Camp Life in the Woods and the Tricks of Trapping and Trap Making - Gibson, W. Hamilton (William Hamilton), 1850-1896 (Salt Lake City, UT : Project Gutenberg, 2005)
"Camp Life in the Woods and the Tricks of Trapping and Trap Making" by W. Hamilton Gibson is a practical guidebook written in the late 19th century. The work focuses on outdoor living skills and the art of trapping, providing detailed instructions for constructing traps and capturing various game animals. The book is aimed primarily at young boys and aspiring trappers, with an overarching theme of engaging with nature in a responsible and educational manner. The opening of this guide introduces its purpose and the author's passion for trapping, emphasizing its importance as a cherished childhood pastime in America, especially for boys in rural settings. Gibson expresses his intent to fill a gap in literature specific to American trapping techniques, advocating for responsible practices. He reinforces that trapping should serve a legitimate purpose rather than be pursued for mere sport. The author outlines the content that will follow, which includes instructions for building shelters, traps, and securing food in the wilderness, thus laying the groundwork for a comprehensive resource on camping and trapping skills. (This is an automatically generated summary.)
Release date is 2005-11-18
Produced by Robert J. Hall
Keywords: Camping; Trapping